Progression and Treatment of Bilateral Knee Bone Marrow Edema Syndrome: A Case Report. Issue 2 (April 2015) - Miranian, Daniel; Lanham, Nathan; Stensby, J. Derek; Diduch, David
Abstract : Case: We report the case of a patient with bilateral multicompartmental bone marrow edema syndrome of the knee, which responded favorably to subchondral core decompression after failing to respond to nonoperative treatment. Conclusion: This case demonstrates that subchondral core decompression can be effective for the treatment of bone marrow edema syndrome.